The Relationship Between Emotion Regulation and Perceived Social Support with Resilience Among Generation Z in Bandung - Muhammad Salma Tegar; Rifqi Farisan Akbar; Prinska Damara Sastri (International Journal of Marketing & Human Resource Research, 2026)
Generation Z is often the subject of public attention, particularly regarding how they respond to challenging situations. Despite various perceptions, Generation Z faces increasingly complex life challenges, making resilience an essential capacity. This study was conducted to further investigate the factors associated with resilience among Generation Z in Bandung, namely emotion regulation and perceived social support. A quantitative correlational design was employed. involving 100 respondents aged 18–28 years who belonged to Generation Z and resided in Bandung were recruited through purposive sampling. Data were gathered using the Connor-Davidson Resilience Scale (CD-RISC), the Emotional Regulation Questionnaire (ERQ), and the Multidimensional Scale of Perceived Social Support (MSPSS) with questionnaires distributed online via Google Forms. The results showed that emotional regulation demonstrated a significant association with resilience (r = 0,550, p <0,05), and perceived social support likewise showed a significant association with resilience (r = 0,493, p <0,05), and both variables jointly demonstrated a significant relations  hip with resilience (R = 0,670, p < 0,05). The present findings suggest that emotion regulation and perceived social support play an important role in shaping resilience among Generation Z in Bandung.